Forming a motivation to the studies by the military-applied exercises for the cadets of few specialties of university of civil defence of Ministry of emergency measures of Ukraine - Konovalov V.V; Poddubny A.G; Poltavec A.I (Kharkov National Pedagogical University, 2013)
The directions of diverse characteristics determine the motivation of students to study military-applied exercises in special training. Questionnaire survey of students of different courses. Found significant differences in the motivation of the students. Proved that the motivation of students during their learning experiences significant changes. The directions of psychological and pedagogical methods to develop positive attitudes of students motivated to learn. Found that first-year students marked inconsistency and instability motivated attitude. Virtually all of the students as the main and most important point to high socially relevant reasons (protection of the homeland, preparing for performance of official duties). However, data from the correlation analysis, we can conclude that these motives are not for real students. Significant impact on the attitude of students to physical perfection is the following factors: ridicule colleagues, they lag behind in physical development. The essential condition is the presence of occupation of free time and comfort.